Sosialisasi Penerapan Strategi Usaha Mikro Kecil dan Menengah pada UMKM di Nagari Simpang Tanjuang Nan Ampek - ., Meswantri; Diana, Yusvi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Community Service Activities are one of the lecturer's Tridharma activities in the form of applying knowledge to the community to provide alternative solutions to problem solving. Community service carried out at MSMEs in Nagari Simpang Tanjuang Nan Ampek aims to analyze internal and external factors as a business strategy in developing MSME activities. The analysis method uses strengths, weaknesses, opportunities and threats (SWOT). The goal is achieved if MSME actors can understand SWOT in developing MSME activities. The result of the service activities carried out is the implementation of business strategies through SWOT analysis so that MSME actors have strategies for developing MSMEs. The contribution of this service activity contributes to MSMEs having a strategy in developing MSME activities.